The effect of mechanochemistry on the preparation of heterogeneous catalysts: Reduction of furfural to obtain furfuryl alcohol. - Pérez-Merchán, Antonio Manuel; Scala, Marcela; Cecilia-Buenestado, Juan Antonio; García-Sancho, Cristina; Malpartida-García, Irene; Mérida-Robles, Josefa María; Moreno-Tost, Ramón; Dimitratos, Nikolaos; Maireles-Torres, Pedro Jesús (My University, 2023)
In this context, mechanochemistry is receiving increasing attention for the synthesis of many chemical compounds in the solid state, considered by IUPAC as one of the 10 methodologies to change the world.Mechanochemistry is the part of chemistry that uses mechanical energy for the transformation of matter. This methodology will be used to study the effect caused by mechanochemistry in the precursor (Mg(OH)2), which is activated at 450 º C to obtain the active phase (MgO). This phase displays Lewis basic sites, which catalyzes the hydrogenation reaction of furfural to furfuryl alcohol. This catalyst will be used in the reduction of furfural to furfuryl alcohol (FFA) using isopropanol as hydrogen donor agent and dissolution medium.
Keywords: Catalizadores; Biomasa vegetal; Mecanoquímica; Furfuryl alcohol; Furfural; Mehanochemistry; Heterogeneous catalysts